Prevention and Intervention in the Risk of Suicide in the Elderly - Elisabete Oliveira; Jorge Oliveira; Júlia Martinho (Medical Sciences Forum, 2022)
The risk of suicide in the elderly is higher than in the general population. Therefore, we aim to provide information that supports nursing decision-making in assessing this risk. Methodologically, we conducted a literature review. We analysed nine articles that supported the model developed in the flowchart divided into three phases: anamnesis, risk analysis and nursing interventions according to weighted risk. As a consequence of COVID-19, it is believed that there is an increase in suffering and the risk of suicide, making it pertinent to disseminate information of quick consultation that supports decision-making in nursing.